Chart Design Considerations for the Navigators of Today and Tomorrow - Kerr, A. J. (The International Hydrographic Review, 2015)
It must be emphasized from the beginning that the ideas and comments in this paper are those of the writer and do not represent any official view. Although the paper may at first appear to discuss some widely separated issues, its main theme is to examine the communications between the nautical chart producer and the chart user. In addition, it will extend itself beyond its title to examine this same mechanism, with respect to the other nautical publications. The paper attempts to stimulate discussion. A potential danger for us all is that we become complacent, claiming that our methods or our products are the best. While self-confidence is desirable, complacency detracts from progress.